Alterations of Bio-elements, Oxidative, and Inflammatory Status in the Zinc Deficiency Model in Rats - Doboszewska, Urszula; Szewczyk, Bernadeta; Sowa-Kućma, Magdalena; Noworyta-Sokołowska, Karolina; Misztak, Paulina; Gołębiowska, Joanna; Młyniec, Katarzyna; Ostachowicz, Beata; Krośniak, Mirosław; Wojtanowska-Krośniak, Agnieszka; Gołembiowska, Krystyna; Lankosz, Marek; et al. (Neurotoxicity research, 2016)
Our previous study showed that dietary zinc restriction induces depression-like behavior with concomitant up-regulation of the N -methyl- d -aspartate receptor (NMDAR). Because metal ions, oxidative stress, and inflammation are involved in depression/NMDAR function, in the present study, bio-elements (zinc, copper, iron, magnesium, and calcium), oxidative (thiobarbituric acid-reactive substances; protein carbonyl content), and inflammatory (IL-1α, IL-1β) factors were measured in serum, hippocampus (Hp), and prefrontal cortex (PFC) of male Sprague–Dawley rats subjected to a zinc-adequate (ZnA) (50 mg Zn/kg) or a zinc-deficient (ZnD) (3 mg Zn/kg) diet for 4 or 6 weeks. Both periods of dietary zinc restriction reduced serum zinc and increased serum iron levels. At 4 weeks, lowered zinc level in the PFC and Hp as well as lowered iron level in the PFC of the ZnD rats was observed. At 6 weeks, however, iron level was increased in the PFC of these rats. Although at 6 weeks zinc level in the PFC did not differ between the ZnA and ZnD rats, extracellular zinc concentration after 100 mM KCl stimulation was reduced in the PFC of the ZnD rats and was accompanied by increased extracellular iron and glutamate levels (as measured by the in vivo microdialysis). The examined oxidative and inflammatory parameters were generally enhanced in the tissue of the ZnD animals. The obtained data suggest dynamic redistribution of bio-elements and enhancement of oxidative/inflammatory parameters after dietary zinc restriction, which may have a link with depression-like behavior/NMDAR function/neurodegeneration.